Qualidade de sementes de milho tratada com ácido salicílico e seus parâmetros produtivos - Ferrazza, Felipe Leandro Felipim (2024)
Corn (Zea mays L.) is one of the most important crops for the world economy, especially for Brazil. Each year, new management technologies are used, such as early sowing, with fewer seeds per meter, which have become frequent and require seeds with greater vigor to obtain good stands and satisfactory productivity. In this context, the exogenous application of salicylic acid (SA) has been used as a technique to minimize the deleterious effects on plants and as an enhancer of the physiological quality of seeds. This work was divided into three articles. The objective of the first article was to evaluate the effect of different concentrations of SA on the physiological and sanitary quality of corn seeds. Seeds of hybrid corn B2315PWU and the following concentrations of SA were used: 0, 500, 1,000, 1,500 and 2,000 uM. The following were evaluated: cold test (vigor); first count; germination; seedling length (aerial and root); dry mass of seedlings and health test. AS did not influence the first count (vigor), germination and cold test (vigor). Dry mass increased linearly with increasing concentration. At concentrations up to 1000 uM, there was an increase in the length of the aerial part and root of corn seedlings. From the control to the concentration of 1000 uM, AS reduced the incidence of fungi in corn seeds. The second article aimed to evaluate the effect of AS on the physiological and health quality of high and low vigor corn seeds. Seeds of the corn hybrid B2315PWU were used, subjected to imbibition at AS concentrations of 0, 500, 1,000, 1,500, 2,000, 2,500, 3,000, 3,500 and 4,000 uM, in high and low vigor seeds. The first count, germination, cold vigor, seedling length and mass, and health test were evaluated. AS doses of up to 2,000 uM improve germination potential. Treatment of corn seeds with AS may be a promising alternative for the control of Fusarium spp. The third article aimed to evaluate the effect of AS applied via corn seeds, at different concentrations and different hybrids, on the physiological, morphological, and productive patterns. Seeds of corn hybrids B2315PWU, B2401PWU, and B2741PWU were used, subjected to AS imbibition at different concentrations, with the treatments being the combination of 3 hybrids and 4 AS doses (0, 1,000, 2,000, and 3,000 uM), totaling 12 treatments. The physiological components of the seeds, plant morphology in the field, and postharvest productivity were evaluated. Doses above 1,000 to 3,000 uM are detrimental to the vigor and germination of corn seeds. AS at doses of 1,000 to 3,000 uM increases the weight of a thousand grains among the hybrids evaluated.